2019
DOI: 10.1002/ceat.201800251
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helical Surface Disc Turbulators on Heat Transfer and Friction Factor Characteristics in the Annuli of a Double‐Pipe Heat Exchanger

Abstract: The heat transfer and pressure drop characteristics in annuli of a double-pipe heat exchanger (DPHE) using helical surface disc turbulators (HSDTs) are experimentally investigated. The effect of a helical surface disc turbulator is studied for three pitch ratios, three diameter ratios, and varying Reynolds numbers. Water flows in the inner tube and air through the annulus. The tests are conducted for air with uniform wall temperature condition. The heat exchanger with the least pitch ratio and least diameter r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 23 publications
(135 reference statements)
0
3
0
Order By: Relevance
“…The strict requirements for heat exchange equipment improvement have led to the development of highperformance heat exchangers. The improvement of heat transfer in pipes has been the subject of numerous studies using a variety of methods, including twisted pipe Ray and Date [1] Yaningsih et al [2] Bellos and Tzivanidis [3] and helical screw Sivashanmugam and Suresh [4] Sadeghi et al [5].The effect of the twisted tape on heat transmission and pressure loss in a heat exchanger was investigated experimentally by Yadav [6]. The dimension of tank (0.8 m x 0.8 m x 1 m)and diameter of tube 5cm with length 1.85m.It depicts that, from results, the heat transfer coefficient increases by 40% with half-length twisted tape inserts when compared with plain heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…The strict requirements for heat exchange equipment improvement have led to the development of highperformance heat exchangers. The improvement of heat transfer in pipes has been the subject of numerous studies using a variety of methods, including twisted pipe Ray and Date [1] Yaningsih et al [2] Bellos and Tzivanidis [3] and helical screw Sivashanmugam and Suresh [4] Sadeghi et al [5].The effect of the twisted tape on heat transmission and pressure loss in a heat exchanger was investigated experimentally by Yadav [6]. The dimension of tank (0.8 m x 0.8 m x 1 m)and diameter of tube 5cm with length 1.85m.It depicts that, from results, the heat transfer coefficient increases by 40% with half-length twisted tape inserts when compared with plain heat exchanger.…”
Section: Introductionmentioning
confidence: 99%
“…They found that an elliptical tube can dramatically increase the comprehensive performance when the shell-side Reynolds number is relatively small. Yadav [11] Many scholars have focused on studying the effects of different heat transfer structures on the performance of heat exchangers, and seldom consider the influence of the external air temperature of the heat exchanger shell on heat exchanger performance. Du [10] investigated continuous helical baffled heat exchangers with different arrangements in inclination angle of the elliptical tube, by using numerical simulation.…”
Section: Introductionmentioning
confidence: 99%
“…They found that an elliptical tube can dramatically increase the comprehensive performance when the shell-side Reynolds number is relatively small. Yadav [11] studied the effect of helical surface disc turbulators on the performance of double-pipe heat exchangers and discovered that a heat exchanger with smaller pitch and diameter had the highest performance. Gu [12] numerically and experimentally investigated the performance of a heat exchanger with a trapezoidal baffle.…”
Section: Introductionmentioning
confidence: 99%